Study on the influence of reservoir impoundment in mountainous areas on mean wind characteristics in bridge site area - Libao Gao; Xi Chen; Zhao Liu; Fu Dai; Suxiang Fu (Advances in Bridge Engineering)
Abstract In Western China, the mountains are high, the canyons are deep, and the wind field features are complex. For the large span bridge in reservoir area, coupled with the large fluctuation of water level, the complexity of wind field of bridge site is further aggravated. The numerical wind tunnel can be used to investigate the effect of water level change on the mountain wind field. However, due to the scale effect, man-made cliffs and the validity of verification, the analysis accuracy remains to be verified. Taking a long-span bridge across a reservoir in a mountainous area as the engineering background, this study systematically compares the influence of transition curve and terrain range, verifies the rationality of numerical simulation through field measurement, and further explores the influence of reservoir filling on the average wind characteristics of the bridge site. The results show that the wind characteristics are strongly affected by the local terrain, the wind direction is basically the same as the strike of the gully, the bridge location is affected by the contraction of the section, and the canyon wind and effect of negative attack angle are significant. After impounding the bridge site, the wind characteristics change obviously, and the canyon wind effect and effect of negative attack angle weaken obviously.